Pegylated liposomal-encapsulated doxorubicin in cutaneous composite lymphoma: A case report - Wollina, Uwe (Medicine (Baltimore), 2016)
BACKGROUND: Cutaneous composite lymphomas are very rare. Their treatment depends upon the different contributing lymphoma entities. Peripheral T-cell lymphoma, not otherwise specified, (PTCL-NOS) represents an aggressive lymphoma subtype. Follicular cutaneous B-cell lymphoma (FCBCL) runs an indolent course. Treatment with pegylated liposomal encapsulated doxorubicin (PLE-DOXO) has yet not been reported in this entity. CASE PRESENTATION: A 73-year-old male patient presented with 3 rapidly growing, painful nodules on his left leg. He was diagnosed as composite cutaneous lymphoma consisting of PTCL-NOS and FCBCL. All lesions had been surgically removed. Staging was unremarkable. After 4 months a relapse occurred with involvement of inguinal lymph nodes and systemic treatment with PEL-DOXO 20 mg/ m(2) every 3 weeks was initiated. After 6 cycles PLE-DOXO, which were well tolerated without grade 3 or 4 toxicities, a mixed response was obtained with complete remission of cutaneous lesions. Lymph nodes were treated by radiotherapy. A second relapse occurred after 8 months and various polychemotherapy regimens were applied without remission. The overall survival was 28 months. CONCLUSION: PEL-DOXO is a possible initial systemic treatment in case of PCTL-NOS. Whether polychemotherapy offers an advantage for survival remains questionable but further investigations are needed.